2004
DOI: 10.1021/ja048432n
|View full text |Cite
|
Sign up to set email alerts
|

A New Synthetic Method for Controlled Polymerization Using a Microfluidic System

Abstract: Polymer materials applications increasingly show sensitivity to single-chain variables such as molecular mass and copolymer composition. [1][2][3] While many parallel synthesis methods developed by the pharmaceutical and life science communities are being applied to polymer synthesis, 4,5 there remains a need to construct polymeric material "libraries" that explore a wide range of polymer structures with accuracy, flexibility, and rapid, often precise, changes.Recent development of various analytical methods, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
101
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(102 citation statements)
references
References 18 publications
1
101
0
Order By: Relevance
“…Most of the work on the microfluidic synthesis of linear polymers was done by radical polymerization or copolymerization, initiated by thermal or photoinitiators [35]. The authors (Wu et al) demonstrated the effect of the flow rate-that is the polymerization time-on the molecular mass of the polymer.…”
Section: Microfluidic-assisted Synthesis Of Polymeric Materialsmentioning
confidence: 99%
“…Most of the work on the microfluidic synthesis of linear polymers was done by radical polymerization or copolymerization, initiated by thermal or photoinitiators [35]. The authors (Wu et al) demonstrated the effect of the flow rate-that is the polymerization time-on the molecular mass of the polymer.…”
Section: Microfluidic-assisted Synthesis Of Polymeric Materialsmentioning
confidence: 99%
“…For high performance, development of new materials and novel fabrication techniques has been actively studied in this area. Synthesis of new materials for nanoimprinting lithography, soft lithography, microfluidic technique, and plastic electronics is of interest for chemists to expand the scope of current nanotechnology to advanced levels [1][2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Microfluidic reactors have been designed then used for synthesis of both organics and inorganics. Recently several groups have reported microfluidic strategies for the synthesis of organic and inorganic materials [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning back mixing, the introduction of a dimensionless number can be useful in order to represent the ratio between the axial dispersion time and the mean residence time, called the Bodenstein number: (65) with axial dispersion (correlated to molecular diffusion, as eq. (66) will show) and mean residence time.…”
Section:  Bodenstein Numbermentioning
confidence: 99%